2020
DOI: 10.1002/adfm.201909267
|View full text |Cite
|
Sign up to set email alerts
|

Defective 2D Covalent Organic Frameworks for Postfunctionalization

Abstract: Defects are deliberately introduced into covalent organic frameworks (COFs) via a three‐component condensation strategy. The defective COFs (dCOF‐NH2‐Xs, X = 20, 40, and 60) possess favorable crystallinity and porosity, as well as have active amine functional groups as anchoring sites for further postfunctionalization. By introducing imidazolium functional groups onto the pore walls of COFs via the Schiff‐base reaction, dCOF‐ImBr‐Xs‐ and dCOF‐ImTFSI‐Xs‐based materials are employed as all‐solid‐state electrolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
107
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(122 citation statements)
references
References 81 publications
2
107
0
1
Order By: Relevance
“…Due to its porous structure and functionalization, perovskite under 353 K and retains 98.3% capacity after 40 cycles with 97.5% coulombic efficiency. [175] In addition, dCOF will have a wide range working temperature range from 303 to 423 K. [175] In the other work, Li et al designed another type of 2D COF (Im-COF-Br) which was synthesized by Schiff base reaction, and the building block is imidazolium-based monomers. This new COF has some charac-teristics, such as positive charge in the COF skeletons, tunable counter-anions, and 5.57 nm pore sizes.…”
Section: Other Type Of Solid-state Electrolytesmentioning
confidence: 99%
“…Due to its porous structure and functionalization, perovskite under 353 K and retains 98.3% capacity after 40 cycles with 97.5% coulombic efficiency. [175] In addition, dCOF will have a wide range working temperature range from 303 to 423 K. [175] In the other work, Li et al designed another type of 2D COF (Im-COF-Br) which was synthesized by Schiff base reaction, and the building block is imidazolium-based monomers. This new COF has some charac-teristics, such as positive charge in the COF skeletons, tunable counter-anions, and 5.57 nm pore sizes.…”
Section: Other Type Of Solid-state Electrolytesmentioning
confidence: 99%
“…[23][24][25][26] Moreover, the uniform open channel of COF networks is benecial for the electrolyte infusion and ion/ electron transport. [27][28][29][30][31] Recently, COFs have been explored as electrode materials for LIBs with improved electrochemical performance compared with traditional small organic compound electrodes. [32][33][34][35] These studies demonstrated that the overall specic capacity of anodes largely relies on the accessible Li-interactive site concentration and the electroconductivity of COFs.…”
Section: Introductionmentioning
confidence: 99%
“…This well-ordered porous structure of TpPa-SO 3 Zn 0.5 could contribute to facilitating uniform and directional ion transport. [27][28][29][30][31][32][33] The stability of TpPa-SO 3 Zn 0.5 in water was evaluated as a requirement for use in aqueous batteries. Aer treatment in H 2 O at 100 C for 7 days, TpPa-SO 3 Zn 0.5 still showed the characteristic XRD pattern (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…COFs have been regarded as appealing ion transport media owing to their ordered porous structure, functionalities and structural stability. [27][28][29][30][31][32][33] A zinc sulfonated COF (TpPa-SO 3 Zn 0.5 ; Fig. 1a) is synthesised to build well-dened directional channels in which covalently tethered and delocalised sulfonates play key roles in realising single Zn 2+ transport.…”
Section: Introductionmentioning
confidence: 99%